2012
DOI: 10.4161/auto.19242
|View full text |Cite
|
Sign up to set email alerts
|

Allophagy

Abstract: In most animals, during oocyte fertilization the spermatozoon provides DNA and centrioles together with some cytoplasm and organelles, but paternal mitochondria are generally eliminated in the embryo. Using the model animal C. elegans we have shown that paternal organelle degradation is dependent on the formation of autophagosomes a few minutes after fertilization. This macroautophagic process is preceded by an active ubiquitination of some spermatozoon-inherited organelles. Analysis of fertilized mouse embryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…However, in recent years different selective forms of autophagy have been identified and characterized, leading to the specific degradation of organelles or pathogens. These selective pathways include the autophagic degradation of mitochondria (mitophagy), peroxisomes (pexophagy), endoplasmic reticulum (reticulophagy or ER-phagy), ribosomes (ribophagy), protein aggregates (aggrephagy), lipid droplets (lipophagy), spermatozoon-inherited organelles following fertilization (allophagy), secretory granules within pancreatic cells (zymophagy), or intracellular pathogens (xenophagy) [ 11 14 ].…”
Section: Types Of Autophagy and Morphologymentioning
confidence: 99%
“…However, in recent years different selective forms of autophagy have been identified and characterized, leading to the specific degradation of organelles or pathogens. These selective pathways include the autophagic degradation of mitochondria (mitophagy), peroxisomes (pexophagy), endoplasmic reticulum (reticulophagy or ER-phagy), ribosomes (ribophagy), protein aggregates (aggrephagy), lipid droplets (lipophagy), spermatozoon-inherited organelles following fertilization (allophagy), secretory granules within pancreatic cells (zymophagy), or intracellular pathogens (xenophagy) [ 11 14 ].…”
Section: Types Of Autophagy and Morphologymentioning
confidence: 99%
“…Degradation of organelles is a common feature for UPI in eukaryotes (1). For example, recent findings in the nematode Caenorhabditis elegans establish the degradation of sperm mitochondria by induction of autophagy (13)(14)(15).…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, autophagy is the primary mechanism for the removal of paternal mitochondria in C. elegans embryos (Al Rawi et al, 2011;Sato & Sato, 2011;Zhou et al, 2011). Lysosomes also participate in the degradation of paternal mitochondria (Sutovsky et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Immediately after fertilization, spermatozoonderived components trigger autophagy in the vicinity of spermatozoon mitochondria in C. elegans. Al Rawi et al (2011) also demonstrated that mouse fertilization induces recruitment of LC3 to the spermatozoon midpiece, indicating that autophagy of paternal mitochondria may be conserved in mammals. Recently, by using two transgenic mouse strains, one bearing green fluorescent protein (GFP)-labelled autophagosomes and the other bearing red fluorescent protein (RFP)-labelled mitochondria, suggested that autophagy is not responsible for the degradation of spermatozoon mitochondria and mtDNA in the mouse embryo after fertilization.…”
Section: Introductionmentioning
confidence: 96%